2011
DOI: 10.4028/www.scientific.net/amr.287-290.2590
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of SiO<sub>2</sub>/PPS Fiber and Study of its Heat-Resistant Properties

Abstract: Through the addition of nano-silicon dioxide in the pure polyphenylene sulfide, the masterbatches were obtained, then using melt spinning technology to prepare SiO2/PPS fiber. The structure and heat-resistant properties of samples were characterized by transmission election microscopy (TEM), infrared spectrum (IR), differential scanning calorimeter (DSC) and other measurements. The experiment results indicate that the mechanical and heat resistance properties of PPS fiber were improved after adding the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Therefore, research about improving the oxidation resistance of PPS has been reported over the last few decades [7,8,9]. Thus far, the methods of antioxidant modification can be mainly divided into two categories: (1) the surface coating method and (2) the direct addition of nanoparticles or antioxidants [6,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, research about improving the oxidation resistance of PPS has been reported over the last few decades [7,8,9]. Thus far, the methods of antioxidant modification can be mainly divided into two categories: (1) the surface coating method and (2) the direct addition of nanoparticles or antioxidants [6,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Various nanoparticles such as silicon carbide (SiC), silicon dioxide (SiO 2 ), montmorillonite (MMT), carbon black, etc. [11,13,14], have been directly added into PPS resin to improve the oxidation resistance. Sugama [9] used octadecylamine as a pretreatment agent to modify montmorillonite (MMT).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy could be related to the different processing method and thermal history of the nanocomposites, which have a strong effect on the final composite properties. On the other hand, very slight s y rises or even some decrements at high loadings have been reported for nanocomposites filled with SiO 2 (Yang et al, 2013;Sheng et al, 2011) (see Table 7.2), attributed to nanoparticle agglomeration. On the other hand, very slight s y rises or even some decrements at high loadings have been reported for nanocomposites filled with SiO 2 (Yang et al, 2013;Sheng et al, 2011) (see Table 7.2), attributed to nanoparticle agglomeration.…”
Section: Static Mechanical Propertiesmentioning
confidence: 96%
“…15 One way to improve the thermal stability and mechanical properties of the PPS polymer is by increasing the specific stiffness and strength of the material by the addition of reinforcing fillers. Examples of reinforcing fillers that have been reported till date include carbon fiber, 16,17 titanium dioxide, 18 silicon dioxide, 19,20 nano copper oxide, 21 hexagonal boron nitride, 22,23 carbon nanotubes, 24 and graphite. 25 Another potential filler in PPS composite that has been least explored in literature is alumina.…”
Section: Introductionmentioning
confidence: 99%